Capital endowments and livelihood security of tribal communities in Central Kashmir - Ishrat F Bhat,; Nasir Husain,; S H Baba, (Agricultural Economics Research Review, 2023)
The tribal communities living on the fringes of forests in Central Kashmir face several positive and negative externalities. Their endowments of livelihood capital, including land, are poor, as are their social bonds. Their livelihoods are insecure, and their food consumption is less than the medical recommendations. Livestock rearing is their most important economic activity. The households in the study area ranked low on the overall livelihood security indices, but households farther away ranked even lower. The livelihood security of tribal households is significantly impacted by the number of workers; security of economic, human, and natural capital; and livestock ownership.